Pelaksanaan Rehabilitasi Sosial kepada Anak Pelaku Tindak Pidana di Lembaga Pemasyarakatan Khusus Anak (LPKA) Kelas II Jayapura (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Children as perpetrators of criminal acts are certainly obliged to be responsible for their actions that have caused harm to others. However, in being responsible for their actions in the Special Correctional Institution for Children, they also need to receive moral guidance to shape their character so that they can behave well during their sentence and when they return to society after serving their sentence. This way, they can socialize well, having gained an understanding of good character formation during their sentence, ensuring they will not commit crimes again. Therefore, the implementation of social rehabilitation to form a quality character for child criminals through community service activities is very important to be carried out. These activities will help restore their social abilities, enabling them to adapt once again and play a positive role in community life. By doing so, they can contribute to society and avoid reoffending, leading to their successful reintegration into the community.